THE ISSUE OF THE RELEVANCE OF THE ISLAMIC EDUCATION CURRICULUM IN THE MERDEKA CURRICULUM - Muchamad Nasrulloh; M. Yahya Ashari (MISBAH : Jurnal Pendidikan dan Pemikiran Islam, 2026)
Characterized by adaptability, essential content, and the strengthening of the Pancasila Student Profile. The Islamic Religious Education (PAI) curriculum is conceptually aligned with this framework, particularly in its goal of nurturing faithful, pious, and morally upright individuals. Nevertheless, practical implementation reveals a discrepancy between the aspirational nature of the policy and the actual conditions on the ground. This study seeks to examine the relevance of the PAI curriculum within the context of the Merdeka Curriculum. Employing a qualitative methodology, the investigation uses a bibliographic approach, examining policy documents, scholarly literature, and findings from previous studies. The research findings illustrate three categories of challenges. The first category pertains to planning issues: educators face obstacles in formulating Teaching Modules, Learning Outcomes (CP), Learning Objectives (TP), and Learning Objective Flows (ATP), alongside an insufficient understanding of diagnostic assessment. The second category addresses implementation challenges: practitioners struggle with applying differentiated instruction, formative-summative assessment techniques, and integrating PAI into the Pancasila Student Profile Strengthening Project (P5). The third category encompasses external factor complications: constraints relating to infrastructure, passive learner characteristics, socio-economic variables in the community, and the limited allocation of 4 teaching hours per week. The study concludes that despite a conceptual alignment between the PAI curriculum and the Merdeka Curriculum, the realization of this potential is hampered by implementation challenges. It is essential to enhance teacher competence, ensure infrastructure availability, develop robust evaluation mechanisms, and strengthen the role of educators and the wider community. Keywords : Challenges, Curriculum Relevance, Islamic Religious Education, Merdeka Curriculum